Knowledge, attitude and practices related to dietary supplements and micronutrients intake among IIUM Kuantan students during the Covid-19 Pandemic - Zahri, Mohamad Zaim; Azahari, Nuraniza (IIUM Press, 2022)
Introduction: The emergence of the COVID-19 Pandemic has fundamentally changed many things, including everyday lifestyle and food habits, particularly during the Movement Control Order (MCO). This is also influencing micronutrient intake due to supplement consumption and limited access to foods, which leads to inadequacy and toxicity of micronutrients causing health complications. This study aims to assess the level of knowledge, attitude and practices related to dietary supplements and micronutrients among IIUM Kuantan students during the COVID-19 Pandemic. Method: 186 IIUM Kuantan students (male: 50.5%) were randomly chosen from each Kuliyyah using a random stratified sampling technique. The questionnaire, which includes sociodemographic data and questions about knowledge, attitudes, and practices, were provided through an online survey to the students. Result: The overall consumption of dietary supplements among the students during the Pandemic (44.6%) increased compared to before COVID-19 (29.0%) occurred. The score of knowledge mean (±SD)and attitude mean (±SD)levels were moderate for both genders. There was a balanced distribution of high and low levels of practice among students mean (±SD), with female students mean (±SD) demonstrating a slightly higher level of practice than male students mean (±SDBesides, vitamins (47.3%) have become the most popular supplement among students and the main reason for general health In addition, there was a significant association between the level of knowledge and attitude (p = 0.001), as well as the level of attitude and practice (p = 0.038). However, there is no association between knowledge and practice. Conclusion: This study indicates that proper education and guidance need to be provided for university students as the majority of KAP scores among male and female students were still at a moderate level.